Intertidal Bryozoa from Korea—new additions to the fauna and a new genus of Bitectiporidae (Cheilostomata) from Baengnyeong Island, Yellow Sea - Min, Bum Sik; Seo, Ji Eun; Grischenko, Andrei V.; Gordon, Dennis P. (Zootaxa, 2017)
Eight species are added to the intertidal bryozoan fauna of South Korea, all collected from the extreme northwestern part of the country at Baengnyeong Island. Five of the species (Hippothoa imperforata, Celleporella hyalina, Celleporella nodasakae, Porella donoghueorum and Suhius rubescentis) are new records. Cauloramphus dicki n. sp., Cauloramphus spencerjonesae n. sp., and Exochella cryptodontia n. sp. are new to science; Suhius n. gen. is a newly recognized genus in Bitectiporidae. The close morphological similarity of umbonuloid-shielded P. donoghueorum to Australasian and Antarctic species of lepralioid-shielded species of Aimulosia is discussed in relation to ascophoran phylogeny. The described cheilostome fauna from South Korea is herein increased to 121 species.